2019
DOI: 10.1111/ecc.13141
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a time out consultation with the general practitioner between diagnosis and start of colorectal cancer treatment: Patient‐reported outcomes

Abstract: Objective To evaluate the introduction of a “time out consultation” with the general practitioner (GP) recommended to patients following the diagnosis of colorectal carcinoma (CRC) before start of treatment. Methods A prospective study using questionnaires to compare the number of GP consultations, with their content and outcomes before and after the introduction of an additional consultation with the GP to improve decision‐making and adequate support. Results 72 patients before and 98 patients after the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
1
17
0
2
Order By: Relevance
“…(17) In addition, previous studies show that cancer patients are more satisfied if the GP is informed about the diagnosis (11) and if there is a contact moment with the GP (a "time out consultation") before start of treatment. (12) Our findings also support and explain the potential positive effect on SDM of actively involving the GP between diagnosis and therapy choice, which was recently reported for palliatively treated cancer patients. (13)…”
Section: Comparison With Existing Literaturesupporting
confidence: 87%
See 2 more Smart Citations
“…(17) In addition, previous studies show that cancer patients are more satisfied if the GP is informed about the diagnosis (11) and if there is a contact moment with the GP (a "time out consultation") before start of treatment. (12) Our findings also support and explain the potential positive effect on SDM of actively involving the GP between diagnosis and therapy choice, which was recently reported for palliatively treated cancer patients. (13)…”
Section: Comparison With Existing Literaturesupporting
confidence: 87%
“…GP support could be enabled to support SDM in the hospital, for instance, by actively offering a 'time-out consultation' with the GP with SDM tools. 12 , 13 , 18 , 19 In addition, cancer patient organisations could support GP involvement by empowering patients to discuss preferred topics with their GP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear indication that our sample suffered from some form of selection bias were the remarkably high scores on the other questionnaires too. Two recent studies in Dutch cancer patients [38, 39] showed substantially lower SDM-Q-9 scores and higher decisional conflict scores. In addition, two recent studies in Dutch cancer patients [40] and Dutch cancer survivors [41] showed somewhat lower patients’ perceived self-efficacy compared to our sample.…”
Section: Discussionmentioning
confidence: 99%
“…At present, radical resection of CRC is the main treatment method for CRC. With the gradual development of radical surgical techniques for CRC, the resection rate and radical treatment rate of CRC increased signi cantly, and the morality rate of patients also decreased signi cantly [1,2]. However, the 5-year survival rate of CRC is still low owing to the metastasis and recurrence after operation.…”
Section: Introductionmentioning
confidence: 99%